A qualitative study of the acceptability of remote electronic bednet use monitoring in Uganda - Sarah M. Alexander; Alfred Agaba; Jeffrey I. Campbell; Nuriat Nambogo; Carol S. Camlin; Mallory Johnson; Grant Dorsey; Kristian R. Olson; David R. Bangsberg; Ryan W. Carroll; Data Santorino; Paul J. Krezanoski (BMC, 2022)
Abstract Background Distribution of long-lasting insecticide treated nets (LLINs) is the most widely used intervention for the prevention of malaria but recall and social desirability biases may lead to challenges in accurately measuring use of bednets. SmartNet is a remote electronic monitor that provides objective measurements of bednet use over weeks at a time. Assessing local acceptability is important when implementing innovative global health technologies such as SmartNet. This study draws on established models such as the Technology Acceptance Model (TAM) and Theoretical Framework of Acceptability (TFA) to assess acceptability of SmartNet in Ugandan households. Methods Semi-structured qualitative interviews were conducted at weeks one and six following installation of SmartNet in ten households in Western Uganda. Heads-of-households answered open-ended questions addressing the main acceptability domains of the TFA and TAM models (i.e. perceived ease of use, ethicality, etc.). Responses were digitally recorded, transcribed, coded and analyzed using a thematic analysis approach. Results Seven out of ten households interviewed reported no difference in use between SmartNet and a standard LLIN. Households stated the large size, soft fabric, and the efficacy of SmartNet relative to a standard LLIN contributed to perceived usefulness and perceived ease of use. Opportunity costs of the novel monitoring system expressed by households included difficulty washing nets and dislike of blinking lights on the device. Barriers to SmartNet use focused on questions of the ethics of bednet use monitoring, discomfort with technical aspects of the device and a poor understanding of its function amongst others in the community. However, explaining SmartNet to other community members resolved these concerns and often resulted in interest and acceptance among peers. Conclusion Objective monitoring of bednet use with SmartNet appears acceptable to these households in Uganda. Use of SmartNet seems to be similar to behaviors around use of standard LLINs. Viewpoints on many aspects of SmartNet were generally favorable. Concerns around ethicality of bednet monitoring are present and indicate the need for continuing community education. The device will continue to be optimized to make it more acceptable to users and to accurately reflect standard LLIN use to improve our understanding of prevention behaviors in malaria endemic settings.